Transcriptomics–metabolomics joint analysis: New highlight into the triterpenoid saponin biosynthesis in quinoa (Chenopodium quinoa Willd.) - Zhao, Yulu; Ma, Yucong; Li, Jiawei; Liu, Bin; Liu, Xiaoqing; Zhang, Jianheng; Zhang, Min; Wang, Chunmei; Zhang, Liping; Lv, Wei; Mu, Guojun (Frontiers in Plant Science, 2022)
Quinoa (Chenopodium quinoa Willd.) is one of the most promising corps for the future. Triterpenoid saponins are the major physiologically active substances of quinoa. Recently, biosynthesis and metabolic pathways related with the triterpenoid saponins in quinoa have attracted increasing research attention. In this study, the seeds of conventional quinoa, NT376-2 (N) and bitter quinoa, B-12071(B) at 30 and 60 DAF (days after flowering) were utilized as the experiment materials, which were determined the content of triterpenoid saponins and used for jointed analysis of transcriptomics- metabolomics. The triterpenoid saponin content of NT376-2 at 30 and 60 DAF compared to B-12071 revealed a significant difference in the N1_vs_B1, N2_vs_B2, N1_vs_N2, and B1_vs_B2, ( p < 0.001). 311 overlapping genes in the above four comparison groups were detected through RNA-seq. KEGG and GO enrichment analysis revealed five metabolic pathways associated with the biosynthesis of triterpenoid saponins in quinoa. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) detected farnesal and ursolic acid, which were identified as the key differential accumulated metabolites (DAMs). Transcriptomics-metabolomics joint analysis revealed that terpenoid backbone biosynthesis (ko00900) and triterpenoid biosynthesis (ko00909) were the enrichment pathways for the generation of triterpenoid saponins in quinoa. Finally, 12 differentially expressed genes (DEGs) were validated with consistent trends in transcriptomics data using quantitative real-time PCR (qRT-PCR), among which the key DEGs associated with the biosynthesis of triterpenoid saponins were CqGGPS, CqFPS1, CqSQS1, CqSQE1 CqSQE3, CqCYP716A15-1, and CqCYP716A15-2. These findings provide an important reference for further investigation on the molecular mechanisms of triterpenoid saponin biosynthesis in quinoa.